Aeration slab study volume 2 - Rahardjo, Harianto (2016)
Volume II of this project report contains an evaluation of the performance of aeration slabs in promoting water and oxygen flows into the root zone and in reducing temperature of the root zone. Installation of aeration slabs is an essential requirement for construction of open space car parks in Singapore as imposed by National Parks Board. The intended objectives of the aeration slabs are to improve water and oxygen flows to the root zone and to reduce the harshness of the environment by planting turf in car park areas. However, there have not been any local empirical data to indicate whether aeration slabs confer significant benefits to trees in car parks. A systematic assessment is therefore required to evaluate the efficacy of aeration slabs in open space car parks. Soil layers below the road, parking lot, and tree pit areas were instrumented for pore-water pressure, water content, temperature, and oxygen concentration measurements. Measurements of local climatic conditions, such as air temperature, relative humidity, potential evaporation, and rainfall above the ground surface were conducted to relate dynamics processes above and below the ground surface. Field instrumentations showed that the air temperature at the instrumented site ranged from 22 to 36°C. The relative humidity ranged from 49.8% to 100%, while the wind speed could reach up to 2.8 m/s. The average daily cumulative potential evaporation was about 4.3 mm/d. A higher frequency of rainfall events occurred between August 2008 and December 2008 and between March 2009 and April 2009, while there was a relatively lower frequency of rainfall between May 2008 and July 2008 and between January 2009 and February 2009. The highest cumulative rainfall throughout the year was 109.8 mm/d. Ground water table was about 5.5 m below the ground surface. Pore-water pressures and volumetric water contents in the soils increased during the wet periods and decreased during the dry periods. Pore-water pressures and volumetric water content of soils under the turf cover were generally higher than those beneath the asphalt pavement and aeration slab. Based on field measurement data supported by numerical analyses, it can be concluded that the pore-water pressure and water content of soils beneath the aeration slab fluctuated slightly more than the soils beneath the asphalt pavement. This would mean that the aeration slab promotes water infiltration slightly better than the asphalt pavement but is likely to be much less effective compared to soil under turf cover. The results of tests on the asphalt pavement showed that it was practically impermeable for water infiltration, whereas the aeration slab has a surface area comprising of 37.8% top soils, which is sufficiently permeable for water flow. The relatively small area in percentage of the permeable top soil layer in the aeration slab, the reduction of rainwater infiltration due to rainwater interception by turf growing in the top soils, and the relatively permeable aggregate layer for lateral water flow were responsible for the similar responses of pore-water pressures and volumetric water contents in the soils under the asphalt pavement and aeration slab during wetting and drying processes. Relative oxygen concentrations of the soils increased during dry periods and decreased during wet periods. Relative oxygen concentrations of the soils under the turf cover were always higher as compared to those under the asphalt pavement and aeration slab. The mean oxygen concentration at 0.25 m, 0.4 m and 0.7 m below the turf cover was 15.3%, 13.2% and 11.6% respectively for soil underneath the turf cover, 12.1%, 6.8% and 0.1% for soil underneath the asphalt pavement and 13.8%, 12.1 and 3.7% for soil underneath the aeration slab. Although the mean oxygen concentration for soil underneath the aeration slab for 0.25 m and 0.4 m depth are higher than the minimum oxygen concentration of 10% required for root growth, the oxygen concentration below the aeration slab went below the minimum oxygen concentration of 10% for 10 months out of the 12 months period of measurement. Temperatures under the turf cover were relatively stable and always lower as compared to those under the asphalt pavement and aeration slab. The mean temperatures for soil underneath the aerations slab were 32.3"C for both 0.125 m and 0.25 m depths whereas the mean temperatures for soil underneath the asphalt pavement were 36.2"C and 35.7°C for 0.125m and 0.25 m depth, respectively. This also indicated that the soil temperatures under the aeration slab were slightly lower than those under the asphalt pavement, but this is likely to be not significant compared to the difference compared to the turf cover. It was demonstrated by means of numerical analyses that relative oxygen concentrations in the soils at the road and parking lot areas decreased significantly when the aeration slabs were replaced with the asphalt pavement. On the other hand, relative oxygen concentrations in the root zones increased significantly when the sub-base and base materials below the asphalt pavement, aeration slab and the root zone under the turf cover were replaced with a soil mixture consisting of 80% granite chips and 20% top soils (80GC-20TS).